Planning, 'politics' and the production of space: the formulation and application of a framework for examining the micropolitics of community place-making. Issue 2 (4th March 2019) - Lennon, Mick; Moore, Dave
ABSTRACT: The theories of Henri Lefebvre on the Production of Space have been influential to our understanding of the ontology of space. This paper complements work which draws on Lefebvre but extends its benefit for planning research through a dialogue with the philosophy of Jacques Rancière. Specifically, the paper formulates a novel investigative framework for examining the micropolitics of the production of space by integrating the work of these philosophers. The analytical benefits of this approach for planning research are illustrated through its application to a case study of community gardening in Dublin, Ireland.